2017
DOI: 10.3961/jpmph.17.044
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Environmental Pollution and Its Impact on Health in China, Japan, and South Korea

Abstract: ObjectivesEnvironmental pollution is a significant global issue. Both objective (scientifically measured) environmental pollution and perceived levels of pollution are important predictors of self-reported health. The purpose of this study was to compare the associations between perceived environmental pollution and health in China, Japan, and South Korea.MethodsData were obtained from the East Asian Social Survey and the Cross-National Survey Data Sets: Health and Society in East Asia, 2010 (n=7938; China, n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…Another study was identified from the recent Internoise 2019 conference [52] giving a total of 34 studies for consideration. Ten studies were excluded as they did not directly measure noise [20,21,[24][25][26][27]35,37], or because no associations between noise exposure and mental health were reported in the paper [29,32] (see Appendix A.2). This left 24 studies for inclusion in the review.…”
Section: Grade Evaluationmentioning
confidence: 99%
“…Another study was identified from the recent Internoise 2019 conference [52] giving a total of 34 studies for consideration. Ten studies were excluded as they did not directly measure noise [20,21,[24][25][26][27]35,37], or because no associations between noise exposure and mental health were reported in the paper [29,32] (see Appendix A.2). This left 24 studies for inclusion in the review.…”
Section: Grade Evaluationmentioning
confidence: 99%
“…Similarly, concerns regarding PM have also grown in Korea over the past several years. 3 According to some surveys, the capital of Korea, Seoul, is a city with a high concentration of PM. Currently, the Korean government and organizations are preparing various policies and regulations regarding PM.…”
Section: Introductionmentioning
confidence: 99%
“…These damaging factors affect population’s health status both physically and psychologically. A recent study showed that physical health is associated with air and noise pollution in Japan, but not in China and South Korea which the authors attributed to the higher expectations of Japanese citizens for a clean environment [ 54 ]. Based on the limited evidence, we tentatively expect that natural environment has greater impact on self-rated health in Japan than in China and Korea.…”
Section: Introductionmentioning
confidence: 99%